ANALYSIS OF MENTAL WORKLOAD ON FORKLIFT OPERATORS DUE TO CHANGES IN ENVIRONMENTAL LIGHT INTENSITY - Nurbi, Rahma Sabilah; Sugiono, Sugiono; Nursasongko, Mega (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
Forklift operation in industrial and warehousing environments often exposes operators to frequent transitions between areas with contrasting light intensities. These abrupt changes in ambient brightness, particularly when moving between indoor and outdoor spaces, can impose significant cognitive demands on operators. This study investigates the impact of fluctuating environmental light conditions on the mental workload experienced by forklift operators and its potential implications for their performance, safety, and well-being. This study uses an experimental design using a driving simulator where respondents are given different light intensities to complete the designed tasks.Â The findings reveal that sudden light fluctuations can temporarily impair visual acuity, depth perception, and contrast sensitivity, necessitating increased cognitive effort to maintain situational awareness, evaluate potential hazards, and navigate safely. Where the respondent's cognitive load was measured using the NASA-TLX questionnaire.Â Furthermore, excessive brightness or glare can cause eye strain, fatigue, and discomfort, exacerbating mental workload. Elevated mental workload due to changing light conditions was found to be associated with diminished situational awareness, impaired decision-making abilities, decreased reaction times, and increased accident risks. Sustained cognitive effort to compensate for visual challenges also contributed to mental fatigue, potentially reducing productivity and operational efficiency. This study highlights the need for appropriate lighting designl modifications to mitigate the mental workload imposed by fluctuating light conditions in forklift operations.